PEMILIHAN KARIER BERDASARKAN GAYA BELAJAR MODEL “KOLB” PADA SISWA CERDAS ISTIMEWA KELAS 12 CERDAS ISTIMEWA BAKAT ISTIMEWA SMAN 1 WONOSARI - Alfiana Rohali; Rochmat Wahab (Universitas Negeri Yogyakarta, 2019)
The aim of this study was to describe of gifted student’s learning style based on the Kolb model learning style in the form of divergers, assimilators, convergers and accommodators and career choice among gifted students. The aspects examined in this study was career choice based on the learning style of the